The Vacuole and Mitochondria Patch (vCLAMP) Protein Mcp1 Is Involved in Maintenance of Mitochondrial Function and Mitophagy in Candida albicans - Mao, Xiaolong; Yang, Li; Fan, Yiming; Wang, Jiazhen; Cui, Dongkai; Yu, Dixiong; Yu, Qilin; Li, Mingchun (Frontiers in Microbiology, 2021)
The vacuole and mitochondria patches (vCLAMPs) are novel membrane contact sites in yeast. However, their role in autophagy has not been elucidated so far. In this article, the role of Mcp1, one core component of vCLAMP, in mitophagy of Candida albicans was investigated. Deletion of MCP1 led to abnormal accumulation of enlarged mitochondria and attenuated stability of mitochondrial DNA (mtDNA) in C. albicans when cultured in non-fermentable carbon sources. Furthermore, the mcp1Δ/Δ mutant exhibited defective growth and degradation of Csp37-GFP. These results indicate that Mcp1 plays a crucial role in mitophagy and maintenance of mitochondrial functions under the non-fermentable condition. Interestingly, this deletion had no impact on degradation of Atg8 (the macroautophagy reporter) and Lap41 (the cytoplasm-to-vacuole targeting pathway marker) under SD-N medium. Moreover, deletion of MCP1 inhibited filamentous growth and impaired virulence of the pathogen. This study provides an insight to vCLAMPs in cellular functions and pathogenicity in C. albicans.